Design of a compact chip filter with two transmission zeros using 0.35 μm GaAs HBT. (January 2020) - Hu, Shanwen; Xu, Kaikai; Hu, Yunqing; Wu, Kejun; Qian, Jinchao; Gao, Yiting; Song, Dingzhou; Wang, Zixuan; Zhou, Bo; Cai, Zhikuang; Guo, Yufeng
Abstract: This paper presents a very compact bandpass filter with two transmission zeros using a commercial GaAs HBT technology. The filter is constructed with two shunt LC tank to generate poles to ensure its passband characteristics, and two series LC tanks to generate zeros at lower and upper stopbands to improve the sideband rejection properties. An additional inductor and capacitor coupling network is employed to achieve good input and output matching without degeneration of the filter selectivity. The filter is designed and fabricated on a 0.35 μm GaAs HBT technology with a chip size of only 0.75 × 0.54 mm 2 . The test results demonstrated that, the center operation frequency of the proposed BPF is 3.45 GHz with a 500 MHz 1-dB bandwidth, the insertion loss is about 2.5 dB, and the sideband rejection is lower than −20 dB at the designed transmission zero frequencies.